Trudy Tashkentskoĭ astronomicheskoĭ observatorii. - Toshkent astronomik observatorii︠a︡si. (Tashkent : Akademii͡a nauk Uzbekskoĭ SSR, 1899)
Atlas in 2 parts accompanies no. 2-3.
Issued also with French title page.
Mode of access: Internet.
First series issued by the observatory under its earlier name: Tashkentskai͡a astronomicheskai͡a i fizicheskai͡a observatorii͡a.
Keywords: Astronomy -- Observations